Titanium alloy with high polishing property and design and preparation method thereof
By adjusting the sintering process, the sintering densification and microstructure optimization of titanium alloy parts are solved, and the problem of insufficient surface polishing performance of titanium alloy in the consumer electronics field is achieved, and the improvement of high polishing performance and cost-effectiveness is achieved.
Patent Information
- Application Number
- CN202411619844.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
Titanium alloys have insufficient surface polishing performance in the consumer electronics field, resulting in poor diffuse reflection and polishing effects, which cannot meet the strict requirements of consumer electronics for high polishing performance.
By adjusting the sintering process, the sintering densification of titanium alloy parts can be realized, and the influence of sintering process on the microstructure of titanium alloy is explored, thereby improving the polishing performance of titanium alloy parts. Specific steps include raw material preparation, premixing, kneading, granulation, injection molding, degreasing, thermal degreasing and sintering.
The density of titanium alloy prepared by powder injection molding exceeds 99.0%, the surface polishing performance is significantly improved, and no other trace elements are introduced or the process flow is increased, reducing costs.
Smart Images

Figure CN119464807A_ABST
Abstract
Description
[Technical field]
[0001] The invention relates to the technical field of powder metallurgy materials, and in particular to a titanium alloy with high polishability and a design and preparation method thereof. [Background technology]
[0002] Titanium and titanium alloys are widely used in aerospace, automotive and medical fields due to their excellent strength, lightweight and corrosion resistance. In recent years, the application of titanium alloys in the field of consumer electronics has gradually increased, covering parts such as smartphone frames, earphone shells, speakers, smart watch cases, and folding screen hinges. Powder injection molding is the main production technology for small and complex consumer electronic parts.
[0003] In the field of consumer electronics, the surface polishing performance of titanium alloy appearance parts is extremely important. Usually, the porosity or low density of titanium alloy products is prone to appear during surface polishing, resulting in diffuse reflection, which seriously affects its polishing effect. In addition, different sintering processes have a significant impact on the microstructure of titanium alloys, which further affects the surface polishing performance of samples. At present, consumer electronic products have put forward more stringent requirements on the surface polishing performance of titanium alloy parts, but relevant research has not been reported.
[0004] Therefore, it is necessary to study a titanium alloy with high polishability and a design and preparation method thereof to cope with the shortcomings of the prior art and to solve or alleviate one or more of the above problems. [Summary of the invention]
[0005] In view of this, the present invention provides a titanium alloy with high polishability and a design and preparation method thereof. By adopting different sintering processes, the sintering densification of titanium alloy parts is achieved, and the influence of the sintering process on the microstructure of the titanium alloy is explored, thereby improving the polishing performance of the titanium alloy parts.
[0006] In one aspect, the present invention provides a method for designing and preparing a titanium alloy with high polishability, the method comprising the following steps:
[0007] Step 1, raw material preparation: prepare appropriate amount of TC4 titanium alloy powder and binder;
[0008] Step 2: premixing: put the titanium alloy powder and the binder into a mixer and premix them in a certain proportion;
[0009] Step 3, kneading: putting the mixed powder of TC4 titanium alloy powder and binder in step 2 into an internal mixer for kneading to obtain feed;
[0010] Step 4, granulation: crushing and granulating the kneaded feed with a granulator;
[0011] Step 5, injection molding: putting the granular feed in step 4 into an injection machine, injecting it with certain injection parameters to obtain an injection green body;
[0012] Step 6, degreasing: solvent degreasing the injection green body in step 5;
[0013] Step 7, thermal debinding: placing the dissolved piece in step 6 into a vacuum sintering furnace for thermal debinding to obtain a sample;
[0014] Step 8, sintering: After thermal degreasing, the sample is heated up and sintered using a certain sintering process to obtain a titanium alloy with high polishability.
[0015] According to the aspects and any possible implementation methods described above, an implementation method is further provided. In step 1, the nominal composition of the titanium alloy powder selected is Ti-6Al-4V, its D50 is 12-20μm, and the oxygen content is 1600-2300ppm; the binder system is wax-based, and its components include paraffin. In step 2, the titanium alloy powder accounts for 56%-70% of the total volume of the mixture, and the rest is wax-based binder. The premixing time is 25 minutes.
[0016] According to the aspects and any possible implementations described above, an implementation is further provided, in step three, the metal powder-wax-based binder mixture is kneaded in an SH-2 atmosphere kneader, the kneading temperature used is 155-165°C, and the kneading time is 1.5-2h.
[0017] According to the aspects and any possible implementation methods described above, an implementation method is further provided, in which the feed obtained in step 4 is granulated in a CF-Ф60 double-wrist extruder granulator, the maximum granulation temperature used is 165°C, the extrusion speed is 10-20Hz, the feeding speed is 5-10Hz, the cutting speed is 5-10Hz, the particle size is 3mm, and the particle length is 2-4mm.
[0018] According to the aspects and any possible implementation methods described above, an implementation method is further provided, in which the feed obtained in step five is injected in an EM120-SVP / 2 Zhenxiong 120-ton injection molding machine, and the injection parameters used are: injection temperature 155-170°C, injection pressure 180-195bar, injection speed 60-80%, and mold temperature 40-60°C.
[0019] According to the aspects and any possible implementation methods described above, an implementation method is further provided, in which the wax-based injection blank obtained in step six is degreased by solvent degreasing + thermal degreasing to obtain a solvent degreased blank, the solvent used is trichloroethylene, and the solvent degreasing parameters are: solvent temperature 40-60°C, and degreasing time is 9-20h.
[0020] According to the aspects and any possible implementation methods described above, an implementation method is further provided, in which the sample after thermal debinding in step seven is subsequently sintered in a furnace, and the sintering process parameters are: heating rate of 2-5°C / min, sintering temperature of 850-1300°C, and holding time of 1-8h.
[0021] According to the aspects and any possible implementation methods described above, an implementation method is further provided, in which the sintered sample obtained in step eight is subjected to metallographic sample preparation and its microstructure is observed, the sample is ground with 240, 400, 800, 1000, 1500, 2000, 3000, and 5000 mesh sandpaper, and then polished, and the sample is wiped and etched with Kroll reagent for 20 to 80 seconds to obtain a metallographic sample.
[0022] According to the above aspects and any possible implementation, an implementation is further provided, wherein the method for designing and preparing a titanium alloy with high polishability further comprises:
[0023] Step 9, density test: the obtained sintered sample is subjected to density test by Archimedes drainage method;
[0024] Step 10, microstructure observation: After metallographic sample preparation, the sintered sample is characterized by scanning electron microscope.
[0025] According to the above aspects and any possible implementation, a titanium alloy with high polishability is further provided, which is prepared by the design and preparation method of the titanium alloy with high polishability, and the titanium alloy has a microstructure density of >99.0%.
[0026] Compared with the prior art, the present invention can achieve the following technical effects:
[0027] 1. The titanium alloy prepared by powder injection molding in the present invention has a density greater than 99.0% and improved surface polishing performance.
[0028] 2. The present invention regulates the sintering structure of powdered titanium alloy by adjusting the sintering process, optimizes the fine-grained equiaxed α-β two-phase structure, thereby improving the polishing performance of titanium alloy parts, without introducing other trace elements or increasing the process flow, so that the cost is effectively reduced.
[0029] Of course, any product implementing the present invention does not necessarily need to achieve all of the above-mentioned technical effects at the same time.
Brief Description of the Drawings
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 is a scanning electron microscope photograph of a sintered tensile bar sample of Example 1 of the present invention;
[0032] Figure 2 Schematic diagram of the polishing effect of the sintered tensile bar sample of Example 1 of the present invention, wherein (a) is with a reference object, and (b) is without a reference object;
[0033] Figure 3 is a scanning electron microscope photograph of a sintered tensile bar sample of Example 2 of the present invention;
[0034] Figure 4 Schematic diagram of the polishing effect of the sintered tensile bar sample of Example 2 of the present invention, wherein (a) is with a reference object and (b) is without a reference object. [Specific implementation method]
[0035] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0036] It should be clear that the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0038] The present invention provides a titanium alloy with high polishability and a design and preparation method thereof, comprising the following steps:
[0039] Step 1, raw material preparation: prepare an appropriate amount of TC4 (Ti-6Al-4V) titanium alloy powder and binder;
[0040] Step 2: premixing: put the metal powder and the binder into a mixer and premix them in a certain proportion;
[0041] Step 3, kneading: putting the mixed powder of the metal powder and the binder in step 2 into an internal mixer for kneading to obtain feed;
[0042] Step 4, granulation: crushing and granulating the kneaded feed with a granulator;
[0043] Step 5, injection molding: putting the granular feed in step 4 into an injection machine, injecting it with certain injection parameters to obtain an injection green body;
[0044] Step 6, degreasing: solvent degreasing the injection green body in step 5;
[0045] Step 7, thermal debinding: placing the dissolved piece in step 6 into a vacuum sintering furnace for thermal debinding to obtain a sample;
[0046] Step 8: Sintering: After thermal debinding, the sample is heated up and sintered using a certain sintering process.
[0047] Step nine, density test: The obtained sintered sample is subjected to density test using the Archimedes drainage method.
[0048] Step 10, microstructure observation: After metallographic sample preparation, the sintered sample is characterized by scanning electron microscope.
[0049] Furthermore, the nominal composition of the titanium alloy powder selected in the above step 1 is Ti-6Al-4V, its D50 is 12-20 μm, and its oxygen content is 1600-2300 ppm; the binder system is wax-based, and its main component is paraffin.
[0050] In a specific embodiment, the titanium alloy powder in the above step 2 accounts for 56%-70% of the total volume of the mixture, and the rest is a wax-based binder. The premixing time is 25 minutes.
[0051] In a specific embodiment, the metal powder-wax-based binder mixture in the above step 2 is kneaded in an SH-2 atmosphere kneader at a kneading temperature of 155-165° C. and a kneading time of 1.5-2 h.
[0052] In a specific embodiment, the feed obtained in the above step three is granulated in a CF-Ф60 double-wrist extruder granulator, the maximum granulation temperature used is 165°C, the extrusion speed is 10-20Hz, the feeding speed is 5-10Hz, the cutting speed is 5-10Hz, the particle size is 3mm, and the particle length is 2-4mm.
[0053] In a specific embodiment, the feed obtained in the above step 4 is injected in an EM120-SVP / 2 Zhenxiong 120-ton injection molding machine, and the injection parameters used are: injection temperature 155-170°C, injection pressure 180-195bar, injection speed 60-80%, and mold temperature 40-60°C.
[0054] In a specific embodiment, the wax-based injection blank obtained in step 5 is degreased by solvent degreasing + thermal degreasing to obtain a solvent degreased blank. The solvent used is trichloroethylene, and the solvent degreasing parameters are: solvent temperature 40-60°C, degreasing time 9-20h.
[0055] In a specific embodiment, the sintering furnace described in step 7 is a BFZS1903111 molybdenum sheet high vacuum sintering furnace, and the solvent debinding blank is subjected to thermal debinding, and the thermal debinding parameters are: a heating rate of 2-5°C / min, and insulation at 300°C, 450°C, and 550°C for 1-2h, respectively. The thermal debinding atmosphere is high-purity argon.
[0056] In a specific embodiment, the sample after thermal debinding in step 7 is then sintered in a vacuum sintering furnace, and the sintering process parameters are: heating rate of 2-5°C / min, sintering temperature of 850-1300°C, and holding time of 1-8h.
[0057] In a specific embodiment, the sintered sample obtained in step eight is subjected to a density test in accordance with the national implementation standard GB / T1423-1996.
[0058] In a specific embodiment, the sintered sample obtained in the above step eight is subjected to metallographic sample preparation and its microstructure is observed. The sample is ground with 240, 400, 800, 1000, 1500, 2000, 3000, and 5000 grit sandpaper, and then polished. Kroll reagent (HF:H 2 SO 4 :H 2 O volume ratio of 1:3:15-30) was used to rub and erode the sample for 20-80 seconds to obtain a metallographic sample. Finally, the prepared metallographic sample was observed using a SU8100 cold field emission scanning electron microscope.
[0059] Example 1
[0060] The preparation method of this embodiment comprises the following steps:
[0061] Step 1, raw material preparation: prepare 2 kg of spherical Ti-6Al-4V titanium alloy powder and a binder, the D50 of the powder is 16.4 μm, and the oxygen content is 1820 ppm; the binder system is wax-based, and its main component is paraffin;
[0062] Step 2, premixing: put the metal powder and the wax-based binder into a mixer and premix them at 64 vol.% for 25 minutes;
[0063] Step 3, kneading: Put the mixture of metal powder and corresponding binder in step 2 into SH-2 atmosphere kneader for kneading to obtain feed. The kneading parameters are: kneading temperature is 160°C, kneading time is 2h;
[0064] Step 4, granulation: the wax-based feed obtained in step 3 is granulated in a CF-Ф60 double-arm extruder granulator, the granulation temperature used is 160°C, the extrusion speed is 15Hz, the feeding speed is 10Hz, the cutting speed is 10Hz, the particle size is 3mm, and the particle length is 4mm;
[0065] Step 5, injection molding: the feed obtained in step 4 is injected in an EM120-SVP / 2 Zhenxiong 120-ton injection molding machine, and the injection parameters used are: injection temperature 165°C, injection pressure 180 bar, injection speed 65%, and mold temperature 50°C;
[0066] Step 6, degreasing: the wax-based injection blank obtained in step 5 is subjected to solvent degreasing to obtain a solvent degreasing blank. The solvent used is trichloroethylene, and the solvent degreasing parameters are: solvent temperature 50°C, degreasing time 18h;
[0067] Step 7, thermal debinding: Place the molten parts in step 6 into a BFZS1903111 molybdenum sheet high vacuum sintering furnace for thermal debinding. The thermal debinding parameters are: heating rate of 3°C / min, and keeping at 300°C, 450°C, and 550°C for 1.5h respectively. The thermal debinding atmosphere is high-purity argon;
[0068] Step 8, sintering: the sample after thermal debinding is then sintered in a vacuum sintering furnace, and the sintering process parameters are: heating rate of 3°C / min, sintering temperature of 1300°C, and holding time of 4h;
[0069] Step 9, density test: The obtained sintered sample is subjected to density test using Archimedes drainage method according to GB / T1423-1996 national implementation standard. The density of the sintered sample is 99.2%;
[0070] Step 10, microstructure observation: The sintered samples obtained in step 8 were subjected to metallographic sample preparation and their microstructures were observed. The samples were ground with 240, 400, 800, 1000, 1500, 2000, 3000, and 5000 grit sandpaper, and then polished. Kroll reagent (HF:H 2 SO 4 :H 2 O volume ratio of 1:3:15-30) was used to rub and etch the sample for 60 seconds to obtain a metallographic sample. Finally, the prepared metallographic sample was observed using a SU8100 cold field emission scanning electron microscope. Figure 1 This is a scanning electron microscope photograph of the sintered part of the tensile bar sample of Example 1 of the present invention, which is a Widmanstatten structure. Figure 2 It is a schematic diagram of the polishing effect of the sintered tensile bar sample of Example 1 of the present invention.
[0071] Example 2
[0072] The preparation method of this embodiment comprises the following steps:
[0073] Step 1, raw material preparation: prepare 2 kg of spherical Ti-6Al-4V titanium alloy powder and a binder, the D50 of the powder is 16.4 μm, and the oxygen content is 1820 ppm; the binder system is wax-based, and its main component is paraffin;
[0074] Step 2, premixing: put the metal powder and the wax-based binder into a mixer and premix them at 64 vol.% for 25 minutes;
[0075] Step 3, kneading: Put the mixture of metal powder and corresponding binder in step 2 into SH-2 atmosphere kneader for kneading to obtain feed. The kneading parameters are: kneading temperature is 160°C, kneading time is 2h;
[0076] Step 4, granulation: the wax-based feed obtained in step 3 is granulated in a CF-Ф60 double-arm extruder granulator, the granulation temperature used is 160°C, the extrusion speed is 15Hz, the feeding speed is 10Hz, the cutting speed is 10Hz, the particle size is 3mm, and the particle length is 4mm;
[0077] Step 5, injection molding: the feed obtained in step 4 is injected in an EM120-SVP / 2 Zhenxiong 120-ton injection molding machine, and the injection parameters used are: injection temperature 165°C, injection pressure 180 bar, injection speed 65%, and mold temperature 50°C;
[0078] Step 6, degreasing: the wax-based injection blank obtained in step 5 is subjected to solvent degreasing to obtain a solvent degreasing blank. The solvent used is trichloroethylene, and the solvent degreasing parameters are: solvent temperature 50°C, degreasing time 18h;
[0079] Step 7, thermal debinding: Place the molten parts in step 6 into a BFZS1903111 molybdenum sheet high vacuum sintering furnace for thermal debinding. The thermal debinding parameters are: heating rate of 3°C / min, and keeping at 300°C, 450°C, and 550°C for 1.5h respectively. The thermal debinding atmosphere is high-purity argon;
[0080] Step 8, sintering: the sample after thermal debinding is then sintered in a vacuum sintering furnace, and the sintering process parameters are: heating rate of 3°C / min, sintering temperature of 900°C, and holding time of 4h;
[0081] Step 9, density test: The obtained sintered sample is subjected to density test using Archimedes drainage method according to GB / T1423-1996 national implementation standard. The density of the sintered sample is 99.3%;
[0082] Step 10, microstructure observation: The sintered samples obtained in step 8 were subjected to metallographic sample preparation and their microstructures were observed. The samples were ground with 240, 400, 800, 1000, 1500, 2000, 3000, and 5000 grit sandpaper, and then polished. Kroll reagent (HF:H 2 SO 4 :H 2 O volume ratio of 1:3:15-30) was used to rub and etch the sample for 60 seconds to obtain a metallographic sample. Finally, the prepared metallographic sample was observed using a SU8100 cold field emission scanning electron microscope. Figure 3 This is a scanning electron microscope photograph of the sintered part of the tensile bar sample of Example 2 of the present invention, which is an equiaxed structure. Figure 4 It is a schematic diagram of the polishing effect of the sintered part of the tensile bar sample of Example 2 of the present invention.
[0083] Example 3
[0084] The preparation method of this embodiment comprises the following steps:
[0085] Step 1, raw material preparation: prepare 2 kg of spherical Ti-6Al-4V titanium alloy powder and a binder, the D50 of the powder is 17.2 μm, and the oxygen content is 1980 ppm; the binder system is wax-based, and its main component is paraffin;
[0086] Step 2, premixing: put the metal powder and the wax-based binder into a mixer and premix them at 64 vol.% for 25 minutes;
[0087] Step 3, kneading: Put the mixture of metal powder and corresponding binder in step 2 into SH-2 atmosphere kneader for kneading to obtain feed. The kneading parameters are: kneading temperature is 160°C, kneading time is 2h;
[0088] Step 4, granulation: the wax-based feed obtained in step 3 is granulated in a CF-Ф60 double-arm extruder granulator, the granulation temperature used is 160°C, the extrusion speed is 15Hz, the feeding speed is 10Hz, the cutting speed is 10Hz, the particle size is 3mm, and the particle length is 4mm;
[0089] Step 5, injection molding: the feed obtained in step 4 is injected in an EM120-SVP / 2 Zhenxiong 120-ton injection molding machine, and the injection parameters used are: injection temperature 165°C, injection pressure 180 bar, injection speed 65%, and mold temperature 50°C;
[0090] Step 6, degreasing: the wax-based injection blank obtained in step 5 is subjected to solvent degreasing to obtain a solvent degreasing blank. The solvent used is trichloroethylene, and the solvent degreasing parameters are: solvent temperature 50°C, degreasing time 18h;
[0091] Step 7, thermal debinding: Place the molten parts in step 6 into a BFZS1903111 molybdenum sheet high vacuum sintering furnace for thermal debinding. The thermal debinding parameters are: heating rate of 3°C / min, and keeping at 300°C, 450°C, and 550°C for 1.5h respectively. The thermal debinding atmosphere is high-purity argon;
[0092] Step 8, sintering: the sample after thermal debinding is then sintered in a vacuum sintering furnace, and the sintering process parameters are: heating rate of 3°C / min, sintering temperature of 950°C, and holding time of 6h;
[0093] Step 9, density test: The obtained sintered sample is subjected to density test using Archimedes drainage method according to GB / T1423-1996 national implementation standard. The density of the sintered sample is 99.4%;
[0094] Step 10, microstructure observation: The sintered samples obtained in step 8 were subjected to metallographic sample preparation and their microstructures were observed. The samples were ground with 240, 400, 800, 1000, 1500, 2000, 3000, and 5000 grit sandpaper, and then polished. Kroll reagent (HF:H 2 SO 4 :H 2 O volume ratio of 1:3:15-30) was used to rub and etch the sample for 60 seconds to obtain a metallographic sample. Finally, the prepared metallographic sample was observed using a SU8100 cold field emission scanning electron microscope.
[0095] Example 4
[0096] The preparation method of this embodiment comprises the following steps:
[0097] Step 1, raw material preparation: prepare 2 kg of spherical Ti-6Al-4V titanium alloy powder and a binder, the D50 of the powder is 17.2 μm, and the oxygen content is 1980 ppm; the binder system is wax-based, and its main component is paraffin;
[0098] Step 2, premixing: put the metal powder and the wax-based binder into a mixer and premix them at 64 vol.% for 25 minutes;
[0099] Step 3, kneading: Put the mixture of metal powder and corresponding binder in step 2 into SH-2 atmosphere kneader for kneading to obtain feed. The kneading parameters are: kneading temperature is 160°C, kneading time is 2h;
[0100] Step 4, granulation: the wax-based feed obtained in step 3 is granulated in a CF-Ф60 double-arm extruder granulator, the granulation temperature used is 160°C, the extrusion speed is 15Hz, the feeding speed is 10Hz, the cutting speed is 10Hz, the particle size is 3mm, and the particle length is 4mm;
[0101] Step 5, injection molding: the feed obtained in step 4 is injected in an EM120-SVP / 2 Zhenxiong 120-ton injection molding machine, and the injection parameters used are: injection temperature 165°C, injection pressure 180 bar, injection speed 65%, and mold temperature 50°C;
[0102] Step 6, degreasing: the wax-based injection blank obtained in step 5 is subjected to solvent degreasing to obtain a solvent degreasing blank. The solvent used is trichloroethylene, and the solvent degreasing parameters are: solvent temperature 50°C, degreasing time 18h;
[0103] Step 7, thermal debinding: Place the molten parts in step 6 into a BFZS1903111 molybdenum sheet high vacuum sintering furnace for thermal debinding. The thermal debinding parameters are: heating rate of 3°C / min, and keeping at 300°C, 450°C, and 550°C for 1.5h respectively. The thermal debinding atmosphere is high-purity argon;
[0104] Step 8, sintering: the sample after thermal debinding is then sintered in a vacuum sintering furnace, and the sintering process parameters are: heating rate of 3°C / min, sintering temperature of 950°C, and holding time of 8h;
[0105] Step 9, density test: The obtained sintered sample is subjected to density test using Archimedes drainage method according to GB / T1423-1996 national implementation standard. The density of the sintered sample is 99.4%;
[0106] Step 10, microstructure observation: The sintered samples obtained in step 8 were subjected to metallographic sample preparation and their microstructures were observed. The samples were ground with 240, 400, 800, 1000, 1500, 2000, 3000, and 5000 grit sandpaper, and then polished. Kroll reagent (HF:H 2 SO 4 :H 2 O volume ratio of 1:3:15-30) was used to rub and etch the sample for 60 seconds to obtain a metallographic sample. Finally, the prepared metallographic sample was observed using a SU8100 cold field emission scanning electron microscope.
[0107] The present invention first mixes Ti-6Al-4V titanium alloy powder with a certain proportion of a binder. Then, the obtained feed is injection molded through an injection machine and a stretching strip mold to obtain a green body. Subsequently, the green body is degreased. Finally, it is sintered in a vacuum sintering furnace with a certain sintering process to obtain a final sintered sample. The present invention achieves the densification of the sintered sample and the regulation of its microstructure by adjusting the sintering process, thereby improving the polishability of the titanium alloy. After the injection molded titanium alloy is sintered, a Widmanstatten structure composed of fine needle-shaped α sheets is likely to appear in the crystal. There is a large internal stress between the uneven tissues, resulting in anisotropy of reflection in different directions, thereby having a negative impact on the overall polishing performance of the part. However, the equiaxed structure obtained by adjusting the process greatly improves the uniformity of the structure, reduces the internal stress, and improves the polishing performance. By optimizing the sintering process, the present invention not only achieves densification, but also indirectly regulates the microstructure of the sample to promote the generation of equiaxed crystals.
[0108] The above is a detailed introduction to a titanium alloy with high polishability and its design and preparation method provided in the embodiment of the present application. The description of the above embodiment is only used to help understand the method and its core idea of the present application; at the same time, for those skilled in the art, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present application.
[0109] For example, certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that hardware manufacturers may use different nouns to refer to the same component. This specification and claims do not use differences in names as a way to distinguish components, but use differences in the functions of components as the criteria for distinction. As mentioned throughout the specification and claims, "including" and "comprising" are open-ended terms, so they should be interpreted as "including / including but not limited to". "Approximately" means that within an acceptable error range, those skilled in the art can solve the technical problem within a certain error range and basically achieve the technical effect. The subsequent description of the specification is a preferred embodiment of the present application, but the description is for the purpose of illustrating the general principles of the present application, and is not used to limit the scope of the present application. The scope of protection of the present application shall be determined by the definition of the attached claims.
[0110] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such a product or system. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the product or system including the elements.
[0111] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0112] The above description shows and describes several preferred embodiments of the present application, but as mentioned above, it should be understood that the present application is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not deviate from the spirit and scope of the present application, and should be within the scope of protection of the claims attached to the present application.
Claims
1. A method for designing and preparing a titanium alloy with high polishability, characterized in that: The design and preparation method comprises the following steps: Step 1, raw material preparation: prepare appropriate amount of TC4 titanium alloy powder and binder; Step 2: premixing: put the titanium alloy powder and the binder into a mixer and premix them in a certain proportion; Step 3, kneading: putting the mixed powder of TC4 titanium alloy powder and binder in step 2 into an internal mixer for kneading to obtain feed; Step 4, granulation: crushing and granulating the kneaded feed with a granulator; Step 5, injection molding: putting the granular feed in step 4 into an injection machine, injecting it with certain injection parameters to obtain an injection green body; Step 6, degreasing: solvent degreasing the injection green body in step 5; Step 7, thermal debinding: placing the dissolved piece in step 6 into a vacuum sintering furnace for thermal debinding to obtain a sample; Step 8, sintering: After thermal degreasing, the sample is heated up and sintered using a certain sintering process to obtain a titanium alloy with high polishability.
2. The method for designing and preparing a titanium alloy with high polishability according to claim 1, characterized in that: The nominal composition of the titanium alloy powder selected in step 1 is Ti-6Al-4V, its D50 is 12-20μm, and the oxygen content is 1600-2300ppm; the binder system is wax-based, and its components include paraffin. The titanium alloy powder in step 2 accounts for 56%-70% of the total volume of the mixture, and the rest is wax-based binder. The premixing time is 25min.
3. The method for designing and preparing a titanium alloy with high polishability according to claim 1, characterized in that: In step 3, the metal powder-wax-based binder mixture is kneaded in an SH-2 atmosphere kneader at a kneading temperature of 155-165° C. and a kneading time of 1.5-2 h.
4. The method for designing and preparing a titanium alloy with high polishability according to claim 1, characterized in that: The feed obtained in step 4 is granulated in a CF-Ф60 double-wrist extruder granulator. The maximum granulation temperature used is 165°C, the extrusion speed is 10-20Hz, the feeding speed is 5-10Hz, the cutting speed is 5-10Hz, the particle size is 3mm, and the particle length is 2-4mm.
5. The method for designing and preparing a titanium alloy with high polishability according to claim 1, characterized in that: The obtained feed material in step 5 is injected in an EM120-SVP / 2 Zhenxiong 120-ton injection molding machine. The injection parameters used are: injection temperature 155-170°C, injection pressure 180-195 bar, injection speed 60-80%, and mold temperature 40-60°C.
6. The method for designing and preparing a titanium alloy with high polishability according to claim 1, characterized in that: The wax-based injection blank obtained in step 6 is degreased by solvent degreasing + thermal degreasing to obtain a solvent degreased blank. The solvent used is trichloroethylene. The solvent degreasing parameters are: solvent temperature 40-60°C, and degreasing time 9-20h.
7. The method for designing and preparing a titanium alloy with high polishability according to claim 1, characterized in that: The sample after thermal debinding in step 7 is then sintered in a furnace, and the sintering process parameters are: heating rate of 2-5°C / min, sintering temperature of 850-1300°C, and holding time of 1-8h.
8. The method for designing and preparing a titanium alloy with high polishability according to claim 1, characterized in that: Step 8: The sintered samples obtained were metallographically prepared and their microstructures were observed. The samples were ground with 240, 400, 800, 1000, 1500, 2000, 3000, and 5000 grit sandpapers, and then polished. The samples were rubbed and etched with Kroll reagent for 20 to 80 seconds to obtain metallographic specimens.
9. The method for designing and preparing a titanium alloy with high polishability according to claim 1, characterized in that: The method for designing and preparing the titanium alloy with high polishability also includes: Step 9, density test: the obtained sintered sample is subjected to density test by Archimedes drainage method; Step 10, microstructure observation: After metallographic sample preparation, the sintered sample is characterized by scanning electron microscope.
10. A titanium alloy with high polishability, prepared by the design and preparation method of a titanium alloy with high polishability according to any one of claims 1 to 9, characterized in that: The titanium alloy structure density is greater than 99.0%.
Citation Information
Cited By
Titanium alloy earphone shell and production method thereof
CN121244962A